Pilot for the Australian Breast Device Registry (ABDR): a national opt-out clinical quality registry for breast device surgery. Issue 12 (28th December 2017) - Hopper, Ingrid; Best, Renee L; McNeil, John J; Mulvany, Catherine M; Moore, Colin C M; Elder, Elisabeth; Pase, Marie; Cooter, Rodney D; Evans, Sue M
Abstract : Purpose: To establish a pilot clinical quality registry (CQR) to monitor the quality of care and device performance for breast device surgery in Australia. Participants: All patients having breast device surgery from contributing hospitals in Australia. A literature review was performed which identified quality indicators for breast device surgery. Findings to date: A pilot CQR was established in 2011 to capture prospective data on breast device surgery. An interim Steering Committee and Management Committee were established to provide clinical governance, and guide quality indicator selection. The registry's minimum dataset was formulated in consultation with stakeholder groups; potential quality indicators were assessed in terms of (1) importance and relevance, (2) usability, (3) feasibility to collect and (4) scientific validity. Data collection was by a two-sided paper-based form with manual data entry. Seven sites were recruited, including one public hospital, four private hospitals and two day surgeries. Patients were recruited and opt-out consent used. Future plans: The pilot breast device registry provides high-quality population-based data. It provides a model for developing a national CQR for breast devices; its minimum dataset and quality indicators reflect the opinions of the broad range of stakeholders. It is easily scalable, and has formed the basis for other international surgical groups establishing similar registries.